The hero's journey: understanding the experiences and motivations of international secondary students. Issue 6 (2nd November 2022) - Sheehan, Helen; Riddle, Stewart
ABSTRACT: This paper examines the utility of Campbell's narrative construction of 'the hero's journey' as a conceptual apparatus to understand how international students from Confucian heritage cultures navigate their experiences in Western schooling systems like Australia. The hero's journey framework was used to investigate the commonalities and differences in international students' beliefs and behaviours, which led to the development of three different students 'hero' models: the self-determined hero, the hesitant hero, and the wounded hero. These models were used to represent the students' beliefs, behaviours and perceptions of support and to describe the experiences and motivations of students in different contexts during their secondary schooling in Australia. The hero's journey provides a potentially useful framework from which to engage schools, systems, and policymakers in productive dialogue regarding the support and engagement of international students.